Editorial: Rapidly Growing Importance of Glycated Haemoglobin (HbA1c) in Diabetic Management - Sandeep Kumar Vashist ,; Khalid Al-Rubeaan, (Journal of Basic & Applied Sciences, 2013)
Glycated Haemoglobin (HbA1c) has become an integral part of glucose management in diabetes mellitus patients as it corresponds to their average blood glucose level in past few weeks. The improved glucose management is clearly apparent to the healthcare professionals from the reduced and sustained HbA1c level in diabetics. HbA1c has also been recently advocated as a diagnostic marker for diabetes mellitus. During the past two decades, tremendous improvements have been made in the development of laboratory-based reference methods for HbA1c analysis and the development of secondary HbA1c reference material that is being used worldwide for the standardisation of HbA1c methods. The current generation of point-of-care (POC) instruments for HbA1c analysis lacks the generally-accepted analytical performance criteria, thereby stressing the need for critical improvement in POC devices and HbA1c methods.